Cost of Production Analysis to Determine the Selling Price of Sweet Bread By Ars Cakery - Andriyanti, Ariska Widya; Kurniawan, Siswandaru (CONSISTENCY: Journal of Communication and Information in Accountancy, 2025)
Purpose – Determining the cost of production is the most important thing in running a business so that the business runs smoothly. Apart from that, it is supported by tight competition between MSMEs in producing products at low prices so it is necessary to calculate the cost of production so that the products produced are valued commensurate with quality and labor. which has been issued. This research aims to find out how to calculate the cost of production to determine the selling price of sweet bread by Ars Cakery. Design/methodology/approach – The research object is Ars Cakery which is located at Jl Lintas Sekayu-Lubuk Linggau, in front of RM Sari Bundo next to Indomaret Kampung Babat, Babat Toman District, Musi Banyuasin Regency, South Sumatra Province. The research method used by the author is descriptive analysis. The data used are primary and secondary data. Primary data was obtained by conducting interviews with the owners of the targeted MSMEs. Secondary data was obtained from reading literature regarding the calculation of the cost of production. Findings – The results of this research state that Ars Cakery determines the selling price at IDR 30,000 per portion. By using the full costing method with a selling price of IDR 30,000, Ars Cakery still makes a profit that can be categorized as quite temporary, even though there was a decline in April due to the effects of the Eid homecoming flow. However, Ars Cakery strives to improve quality and quality at prices that do not strangle consumers.